PENGARUH MODEL PBL BERBANTU WORDWALL TERHADAP HASIL BELAJAR IPAS SISWA KELAS V SDN 48 PEKANBARU - sitorus, nita safitri; Lingga, Leny Julia (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the effect of using the Problem Based Learning (PBL) model assisted by Wordwall media on the learning outcomes of fifth-grade students in the IPAS subject at SDN 48 Pekanbaru. The background of this research is based on the low student learning outcomes due to the lack of interactive learning media and the monotonous use of conventional teaching methods. This research employed a quantitative approach with a pre-experimental design, specifically the One Group Pretest-Posttest Design. The sample consisted of 40 students from class VA. The research instrument was a cognitive-based learning outcome test in the form of 20 multiple-choice questions, validated by content and instrument experts. Data were analyzed using the paired sample t-test with the assistance of SPSS version 27. The results showed an increase in the average learning scores from 10.83 in the pretest to 14.83 in the posttest. The significance value (Sig. 2-tailed) in the paired sample t-test was 0.000 < 0.05, indicating a statistically significant difference between the pretest and posttest scores. Thus, the PBL model assisted by Wordwall is proven to be effective in improving students' learning outcomes. The application of this model creates a more engaging and interactive learning environment and encourages active student participation, positively impacting the improvement of IPAS learning outcomes.